Theoretical investigation of electronic structure and thermoelectric properties of MX2 (M=Zr, Hf; X=S, Se) van der Waals heterostructures. (March 2019) - Khan, Fawad; Din, H.U.; Khan, S.A.; Rehman, G.; Bilal, M.; Nguyen, Chuong V.; Ahmad, Iftikhar; Gan, Li-Yong; Amin, B.
Abstract: In this paper, van der Waals heterostructures consisting of MX2 (M = Zr, Hf and X = S, Se) monolayers are modeled. The favorable stacking and stability of the modeled monolayer heterostructures are confirmed through binding energy and phonon dispersion calculations. After confirming stability, the electronic and thermoelectric properties of these compounds are explored using the first-principles calculations combined with semiclassical Boltzmann transport theory. It is found that type-II band alignment in ZrS2 HfSe2 facilitates charge separation for optoelectronics and solar energy conversion. All studied heterostructures show remarkably higher electrical conductivity than corresponding monolayers, responsible for large power factor values, especially at 1200 K. These findings indicate that the creation of van der Waals heterostructures from MX2 may be promising for efficient optoelectronic and thermoelectric devices. Highlights: First-principles study of structural, electronic and thermoelectric performance of van der Waals heterostructures of MX2 (M = Zr, Hf and X = S, Se) monolayers. Dynamical stability of all under study heterostructures. Type-II band alignment in ZrS2 -HfSe2 . van der Waals heterostructures of MX2 (M = Zr, Hf and X = S, Se) are promising for efficient optoelectronic and thermoelectric devices.